Institutional strength, peacebuilding, and productive entrepreneurship-exploratory analysis in Colombia (2018)
After more than half a century of armed conflict, Colombia is moving towards a post-conflict period. National and regional strategies aimed to strengthen institutional capacities, promote productive entrepreneurship and reduce organized violence and crime, are crucial lines of action for the alleviation of current (and future) grievances among ex-combatants, and Colombian society in general. This study presents an exploratory analysis on institutional strength, peacebuilding, and productive entrepreneurship in Colombia. Three composite indices based upon international assessments or seminal studies were developed, namely: Institutional Strength Index; Building Peace Index (based on the Negative Peace Index and Positive Peace Index); and Productive Entrepreneurship Index. The results showed a significant correlation between Institutional Strength Index and Productive Entrepreneurship Index. Population is the variable with the most significant correlation with productive entrepreneurship, employment, GDP, industrial sophistication, innovation, crime and certain types of violence (sexual and domestic). © 2018 The Authors. Published by VGTU Press.